Political violence problematic in the Arab world - النداف فارس; حمود منار علي (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This study dealt with the problem of political violence in the Arab world. It focused on monitoring, analyses and presentation of political violence phenomena inside the Arab countries through answering the following questions. - Is the political violence in the Arab world the result of the contrast or conflicts that are in the political system.? - Is the violence the result of the misjudgment that Arab people suffer from.? The importance of the basic reasons for this study is that it studies the most important factors that directly and indirectly contributed to the escalation of the phenomenon of political violence in its various forms. The study started with identifying the political violence then describing it’s causes that are various cultural, economic and its forms and its important types in addition to the economic, political and social reflections of the political violence on the Arab world.